Electronic structure and magnetic properties of the Mg-rich intermetallic NdNiMg5 by hybrid density functional theory. (December 2020) - Mehmood, Shahid; Ali, Zahid; Sadiq, Muhammad; Khan, Imad; Ahmad, Iftikhar
Abstract: Mg-rich intermetallic NdNiMg5 in orthorhombic phase with space group Cmcm (No. 63) has been studied theoretically using hybrid functional (HF–B3PW91) within the frame work of density functional theory (DFT). The calculated structural parameters and geometries are found in good agreement with the experiments. The electronic properties of the material reveal the metallic nature. Nd 4f-states splitting show that A2, y[t1 ] and z[t1 ] contributed in the valence band; x[t1 ], ksi[t2 ] and eta[t2 ] in conduction band; where zeta[t1 ] state completely lay at the Fermi level make the compound metallic. The electrical properties show that the material has significant conductivity above the room temperature. The stable magnetic phase of the compound is optimized which show that the material is stable in G-type antiferromagnetic (AFM) phase and Nd–Ni direct magnetic exchange interactions are involved. The calculated effective magnetic moments of Nd is 3.70 μB per unit cell. The post-DFT calculations also confirm the AFM phase of the compound with Neel temperature (TN ) = 25 K and Curie-Weiss constant (θ) = −23 K. Based on the above physical properties it is expected that this intermetallic could be used in spin valve and magnetic memory devices. Highlights: Mg-rich intermetallic NdNiMg5 has been investigated theoretically using hybrid density functional theory. The electronic properties of the material reveal the metallic nature. The electrical properties show that the material has significant conductivity above the room temperature. Stable magnetic phase of the compound is G-type anti-ferromagnetic phase. The post-DFT calculations also confirm the AFM phase of the compound.